Wearable respiratory sensors for COVID‐19 monitoring. Issue 5 (31st October 2022) - Chen, Guorui; Shen, Sophia; Tat, Trinny; Zhao, Xun; Zhou, Yihao; Fang, Yunsheng; Chen, Jun
Abstract: Since its outbreak in 2019, COVID‐19 becomes a pandemic, severely burdening the public healthcare systems and causing an economic burden. Thus, societies around the world are prioritizing a return to normal. However, fighting the recession could rekindle the pandemic owing to the lightning‐fast transmission rate of SARS‐CoV‐2. Furthermore, many of those who are infected remain asymptomatic for several days, leading to the increased possibility of unintended transmission of the virus. Thus, developing rigorous and universal testing technologies to continuously detect COVID‐19 for entire populations remains a critical challenge that needs to be overcome. Wearable respiratory sensors can monitor biomechanical signals such as the abnormities in respiratory rate and cough frequency caused by COVID‐19, as well as biochemical signals such as viral biomarkers from exhaled breaths. The point‐of‐care system enabled by advanced respiratory sensors is expected to promote better control of the pandemic by providing an accessible, continuous, widespread, noninvasive, and reliable solution for COVID‐19 diagnosis, monitoring, and management. Abstract : Wearable respiratory sensors can monitor biomechanical signals such as the abnormities in respiratory rate and cough frequency caused by COVID‐19, as well as biochemical signals such as virus biomarkers from exhaled breaths. The point‐of‐care system enabled by advanced wearable respiratory sensors is expected to promote better control of the pandemic by providing an accessible, continuous, widespread, noninvasive, and reliable solution for COVID‐19 diagnosis, monitoring, and management.